PENGEMBANGAN MEDIA KOMIK PADA MATERI SUMBER ENERGI TERHADAP HASIL BELAJAR KELAS III SD NEGERI 3 RAMBUTAN - Kurnia, Kurnia; Retta, Allen Marga; Ayurachmawati, Puji (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2024)
The aim of the research is to develop comic media to determine the validity, practicality and potential effects of the comic media being developed. The type of research applied is Research and Development (R&D) with the ADDIE method which consists of Analyze, Design, Development, Implementation and Evaluation. The research results from the development of comic media on energy source materials were valid. It can be seen from the assessment results from media, material and language experts, obtaining a percentage of 87% with the criteria "Very Valid". Based on the value given by the validator, comic media can be stated valid to be used in the learning process. The results of the development of comic media can be seen from the student responses in the one to one trial which obtained a percentage of 8.3% with the "Very Practical" criterion, while the student response in the small group trial obtained a percentage of 8.8% with the "Very Practical" criterion", and student responses in the field test which obtained a percentage of 8.7% with the criteria "Very Practical" based on responses from students, the comic media can be stated to have practicality. The results of developing comic media were stated effective. It can be seen from the results of research in field trials which obtained a pre-test score of 7.9% and a post-test score of 9.1% with the criteria "Very Highâ€.